Rhodamin B Degradation Using Fe-Alginate Gel Beads under UV Light Exposure - Andreas, Roy; Setyaningtyas, Tien; Riyani, Kapti (Universitas Sarjanawiyata Tamansiswa, 2024)
Heterogeneous Fenton can solve the problem in classic Fenton which is a homogeneous catalyst. Some of the problems with classic Fenton contained sludge production, lost catalysts, and no reuse. This study focuses on the application of Fe-alginate gel beads in the photo-Fenton system using UV light to degrade the dye rhodamine B. After the synthesis step of Fe-alginate gel beads, beads are used to degrade rhodamine B. In addition, the rate of kinetics, mechanism tests, and the reusable tests of Fe-alginate gel beads was also observed. The results confirmed that the degradation value of rhodamine B is 98.8% with the photocatalytic activity is 88.8%. This heterogenous Fenton system fits in first order and •OH is the main radical species to degrade rhodamine B. The reuseable Fe-alginate gel beads were taken out five times, and showed a degradation value of more than 90%. Therefore, it can confirm that the usage of Fe-alginate gel beads as a heterogeneous Fenton may be applied to industrial wastewater processing containing dyes or organic pollutants because this photo-Fenton system is low cost and also be able on visible light.